Proteomic and transcriptomic analyses of protein biomarkers during early hyperinfection in strongyloidiasis - Al-Zihiry, Khalid Jameel Kadhim (2016)
Strongyloides stercoralis is the most common intestinal nematode in humans, and it infects millions of people worldwide. This infection results in asymptomatic chronic disease that may remain undetectable. Its unique ability to proliferate within the host can cause a hyperinfection syndrome and dissemination of infective larvae in individuals with impaired cell-mediated immunity, thus increasing the mortality rate up to 87%. The diagnosis of hyperinfection syndrome is difficult to establish and entails a high level of suspicion. The main objective of the current study was to identify specific protein biomarkers from the excretory/secretory (ES) products of the infective filariform larva and from the serum proteins of infected Wistar rats that can be used as diagnostic indicators for early hyperinfection syndrome in strongyloidiasis. In this study, S. ratti, which is an animal parasite similar to S. stercoralis and commonly used in research related to S. stercoralis, was used as a model. Seventy wild rats, Rattus norvegicus, were trapped from different locations in the Serdang areas and were brought back to the Animal Experimental Unit and Medical Parasitology and Entomology Lab in UPM for further examination. S. ratti was detected in 34.2% of the trapped wild rats by using different conventional parasitological techniques and this was then reconfirmed by using Polymerase chain reaction (PCR) methods. A PCR method targeting the rRNA gene of the species of Strongyloides was conducted based on the published universal primers for the detection of S. ratti in faecal samples of wild rats. Strongyloides ratti was then isolated from the wild rats and new colonies were established and maintained in laboratory bred Wistar rats for the continuous supply of S. ratti. Faecal pellets from infected Wistar rats were collected and cultured using Modified Faecal Filtration Culture technique (MFFC) for the harvesting of high quality and quantity of infective filariform larvae (L3) used for this research. An experimental study was performed to induce hyperinfection syndrome and dissemination of L3 larvae of S. ratti in experimentally immunosuppressed Wistar rats using prednisolone, a corticosteroid immunosuppressive drug to validate that the pathological changes that occurred were similar between the Wistar rat and human strongyloidiasis. Infected Wistar rats were sacrificed and tissue samples were collected for histopathology study. Prednisolone treatment resulted in a dramatic increase in the infection intensities as proved by the increased in eggs and larval output, and adult recovery that exceeded the inoculated doses. The results of the histopathology study showed dissemination of infective filariform larvae mainly in the tissues of the lungs and liver because of an increased parasite burden during hyperinfection and disseminated strongyloidiasis. These observations were similar to human strongyloidiasis under immunosuppressive or anti-inflammatory regimens, including corticosteroid therapies. In this study, the Wistar rats were divided into two main groups, the first group was infected with S. ratti but without giving prednisolone (non-treated group) and the second group was infected with S. ratti and treated with prednisolone (treated group). Excretory/secretory (ES) products from the filariform larvae and blood serum from the non-treated Wistar rats and the Wistar rats treated with 4.5 mg/kg prednisolone were analysed in one-dimensional and two-dimensional gel electrophoresis (1D, 2D), LC-MS/MS and MALDI-TOF/TOF MS. A total of 10 protein biomarkers were detected as overexpressed from a treated ES product with molecular weights ranging from 30-90 kDa and isoelectric points ranging from 3-11, as well as 8 overexpressed protein biomarkers which were detected from treated Wistar rat sera. Relative semi-quantitative real-time PCR (qPCR) with SYBR Green was performed using a Mastercycler Realplex to compare the expression level of the detected biokmaker’s genes between treated and non-treated groups. These genes were selected based on proteomics results and are representing respective protein that have identified earlier, in order to validate the related expressed protein biomarkers. Nine related genes were identified which showed significantly higher expression levels to the related identified biomarkers, whereas one gene (Arg) recorded down regulation in its expression. The study concluded that, 18 protein biomarkers were successfully identified and could be used as diagnostic biomarkers during early hyperinfection syndrome in strongyloidiasis.